High-throughput electron tomography identifies centriole over-elongation as an early event in plasma cell disorders - Köhrer, Sebastian; Dittrich, Tobias; Schorb, Martin; Weinhold, Niels; Haberbosch, Isabella; Börmel, Mandy; Pajor, Gabor; Goldschmidt, Hartmut; Müller-Tidow, Carsten; Raab, Marc-Steffen; John, Lukas; Seckinger, Anja; et al. (Leukemia, 2023)
Plasma cell disorders are clonal outgrowths of pre-malignant or malignant plasma cells, characterized by extensive chromosomal aberrations. Centrosome abnormalities are a major driver of chromosomal instability in cancer but their origin, incidence, and composition in primary tumor cells is poorly understood. Using cutting-edge, semi-automated high-throughput electron tomography, we characterized at nanoscale 1386 centrioles in CD138pos plasma cells from eight healthy donors and 21 patients with plasma cell disorders, and 722 centrioles from different control populations. In plasma cells from healthy individuals, over-elongated centrioles accumulated with age. In plasma cell disorders, centriole over-elongation was notably frequent in early, pre-malignant disease stages, became less pronounced in overt multiple myeloma, and almost entirely disappeared in aggressive plasma cell leukemia. Centrioles in other types of patient-derived B cell neoplasms showed no over-elongation. In contrast to current belief, centriole length appears to be highly variable in long-lived, healthy plasma cells, and over-elongation and structural aberrations are common in this cell type. Our data suggest that structural centrosome aberrations accumulate with age in healthy CD138pos plasma cells and may thus play an important role in early aneuploidization as an oncogenic driver in plasma cell disorders.